Penyuluhan Hukum Tentang Penyelesaian Sangketa Perkawinan Dengan Menggunakan Pranata Adat Saudara Kawin Di Pulau Haruku Kabupaten Maluku Tengah - Barzah Latupono; Sarah Selfina Kuahaty; Theresia Louize Pesulima (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The rise of marriages carried out without going through the marriage procedures in the Marriage Law has resulted in many problems regarding the validity of marriages in Central Maluku district, giving rise to various legal problems in the local community.Purposes of Devotion: To provide legal understanding related to marriage issues that can be resolved by married siblings without having to go to court in Pulau Haruku District, Central Maluku Regency. Method of Devotion: Carried out using the lecture method by each presenter. The lecturer is given time to present the material, after that the participants are invited to ask problems or questions, which are then answered in turn by the presenter according to the problem being asked.Results of the Devotion: It is important for all levels of society to understand Marriage Law and that problems that arise can be resolved by married relatives as mediators so that marriage problems no longer have to be resolved in court.